Results of Indoor Hockey Training on Mastery of Dribble Techniques in Hockey Games - Khairul Ahmad; Ade Rahmat; Ashadi Cahyadi (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2024)
The purpose of the study. Mastery of fundamental techniques in hockey is essential for players. Mastery enables player cooperation to achieve the game's objective. Key techniques include dribbling and pushing the ball, applicable in both indoor and field hockey. These techniques are vital for effective gameplay. In indoor hockey, only dribbling techniques are permitted according to regulations. Practice enhances dribbling skills, requiring repetitive training. This study aims to compare indoor and field hockey training effectiveness on dribbling mastery. Materials and methods. An experimental method was employed, utilizing 24 athletes from Sambas Hockey Club, divided into two groups. Results. The results indicate a significant improvement in dribbling technique mastery in the indoor training group. Conclusions. The research concludes that indoor hockey training significantly enhances basic dribbling technique mastery compared to field hockey training.